METODE KAMPANYE PROMOSI DALAM MENARIK MINAT MAHASISWA BARU DI UNIS TANGERANG - Andini, Monika Yulia; Suseno, Ari; Jeffri, Suci Emelsi (Statement: Jurnal Media Informasi Sosial dan Pendidikan, 2024)
Competition in the world of education is currently increasing, one of which is at the university level, both private and public. Factors that inhibit a person's interest in continuing to college are the high cost of education, the interest in learning and academic achievement obtained by students, and the lack of maximum socialization of higher education to students in schools. The purpose of this study is to understand how the methods and obstacles of promotional campaigns at UNIS Tangerang. This research uses descriptive qualitative methods and will be studied with the theory of integrated marketing communication (IMC) which has several indicators, namely, Advertising, Direct Marketing, Sales Promotion, Public Relations, Events & Experiences, and Personal Selling. This study found that the promotion team of Syekh-Yusuf Islamic University Tangerang has implemented all indicators of the IMC (Integrated Marketing Communication) theory. The conclusion of this study shows that the implementation carried out by the promotion team of Syekh-Yusuf Islamic University Tangerang in the application of marketing communication, namely the most effective of all indicators is Sales Promotion